Assessment of quality of life of patients with oral sub mucous fibrosis before and after treatment with topical curcumin - Patil Neha; Khandelwal P. N.; Patel Shilpa; Gupta Bharat (EDP Sciences, 2022)
Background and aim: Oral Submucous Fibrosis (OSMF) is potentially pre-malignant condition of the oral cavity with a high malignant transformation rate. The condition not only affects the oral function of the patients but has a huge impact on their social and psychological wellbeing affecting the overall quality of life. To evaluate the effectivity of the treatment assessing the quality of the life of these patients before and after treatment is of utmost importance but till now has not been an integral part of the management strategy. This study was carried to assess the change in quality of life before and after treatment with curcumin in patients with OSMF. Methods: Quality of life was assessed before and after 3 months of treatment with topical curcumin in 50 patients with OSMF using European Organization for Research and Treatment of Cancer Quality of Life head and neck Questionnaire (EORTC QLQ35). Results: At the end of 3 months there was significant (p < 0.05) change in the quality of life of patients with OSMF as suggested by assessment of the multi-item and single item scale used in the questionnaire. Conclusion: The study emphasizes the use of assessing Quality of life as an integral part of treatment strategy for OSMF and suggests curcumin as a promising treatment modality for patients with OSMF.